Kekuatan Social Media dan Word Of Mouth dalam Mempengaruhi Keputusan Pembelian Konsumen pada Restorant Mie Seuhah PISAN (MIE SP) Sukabumi - Adelia Athaya Dzakiyyah; Nor Norisanti; Acep Syamsudin (Journal of Management and Bussines (JOMB), 2020)
The purpose of this study was to measure the strength of social media and word of mouth on consumer purchasing decisions at Mie SP Sukabumi restaurant. The method used in this research is associative descriptive and quantitative approaches with multiple linear regression as data analysis techniques. The results of this study indicate that the total effect simultaneously is only 4.5% while the remaining 95.5% is influenced by other variables not examined in this study. Conclusion, social media does not have a positive and significant influence on purchasing decisions, while word of mouth has an influence on purchasing decisions partially. Keywords: Purchase Decision, Social Media, Word of Mouth